PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSETS PADA PT ACE HARDWARE INDONESIA TBK PERIODE TAHUN 2012-2021 - Rizka Wahyuni Amelia; Teguh Purnama (Journal of Research and Publication Innovation, 2023)
This study aims to determine the effect of Current Ratio (CR), and Debt To Equity Ratio (DER) on Return On Assets (ROA) at PT. Ace Hardware Indonesia Tbk Year 2012 – 2021 either partially or simultaneously. The research method uses quantitative descriptive methods with hypothesis testing. The sample used in this study is the financial statements of PT. Ace Hardware Indonesia Tbk in 2012 –2021. The analytical method used is Descriptive Statistical Analysis, Classical Assumption Test with Normality Test method, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, Simple Linear Regression Test, Regression Test Multiple Linear, Correlation Coefficient Test, Determination Test, T Test, and F Test. From the results of this study obtained fluctuating data. Partially Current Ratio (CR) has effect on Return On Assets (ROA), with the results obtained tcount -3,507 > ttable 2.365 with a significant value of 0,010 <0.05. While the Debt to Equity Ratio (DER) has effect on Return On Assets (ROA), with the results obtained tcount -6,111 > ttable 2.365 with a significant value of 0,000 < 0.05. Simultaneously the variables Current Ratio (CR) and Debt to Equity Ratio (DER) has effect on Return On Assets (ROA), with the results obtained Fcount 22,354 > Ftable 4.74 with a significance of 0,001 < 0.05 and the independent variable consisting of CR and DER contributed 86,5% to ROA, while the remaining 13,5% was influenced by other factors not explained in this study.